Social Media Marketing, Brand Awareness, and Student Enrollment Decisions: The Mediating Role of Perceived Value - Zulham Dwi Pratikto; Ratih Nur Setyaningsih (IJBLE Scientific Publications Community Inc., 2026)
Private higher education institutions increasingly depend on digital communication to compete for prospective students, yet the mechanism through which social media marketing translates into enrollment decisions remains insufficiently understood. This study examined the direct effects of social media marketing and brand awareness on student enrollment decisions and assessed perceived value as a mediating mechanism. A cross-sectional survey was administered to 170 prospective students selected through purposive sampling. The constructs were measured using a five-point Likert scale, and the data were analyzed in SPSS using multiple linear regression and a causal-steps mediation procedure. Perceived value showed the strongest positive association with enrollment decisions (coefficient = 0.580, p < .001), followed by brand awareness (coefficient = 0.255, p < .001). Social media marketing did not have a statistically significant direct association with enrollment decisions (coefficient = 0.053, p = .233), although it significantly predicted perceived value. The model explained 69.7% of the variance in enrollment decisions (R² = .697; F(3, 166) = 127.485, p < .001). Under the mediation criterion adopted in this study, the results are consistent with complete mediation: social media marketing appears to influence enrollment decisions primarily by strengthening prospective students’ perceptions of institutional value. The findings indicate that universities should prioritize credible value communication and sustained brand salience rather than relying on promotional exposure alone.